Evaluating touch-screen vibration modality for blind users to access simple shapes and graphics. Issue 110 (February 2018) - Tekli, Joe; Issa, Youssef Bou; Chbeir, Richard
Abstract: Accessing visual information becomes a central need for all kinds of tasks and users (from accessing graphics and charts in news articles, to viewing images of items on sale on e-commerce sites), especially for blind users. In this context, digital tools of assistance, using adapted software (screen readers, talking browsers, etc.), hardware (force feedback mouse, piezo-electric pins, etc.), and more recently touch-screen technology (using smart phones or smart tablets) have been increasingly helping blind persons access and manipulate information. While effective with textual information, yet existing solutions remain limited when handling visual information. In this context, the goal of our study is to shed light on how the vibration modality can be perceived by blind users when accessing simple contour-based images and visual graphics on a touch-screen. In this paper, we target the vibration-only modality, compared with audio-kinesthetic or multimodal vibro-audio solutions. Our main motivation is that the potentials and limitations of touch-screen vibration-only feedback need to be fully studied and understood prior to integrating other modalities (such as sound, human speech, or other forms of haptic feedback). This could prove very useful in a range of applications: allowing blind people to access geographic maps, to navigate autonomously inside and outside buildings, as well as to access graphs and mathematical charts (for blind students). To achieve our goal, we develop a dedicated experimental protocol, titled EVIAC, testing a blind user's capacity in learning, distinguishing, identifying, and recognizing basic shapes and geometric objects presented on a vibrating touch-screen. Extensive tests were conducted on blindfolded and blind candidates, using a battery of evaluation metrics including: i) accuracy of shape recognition, ii) testers' average response time, iii) number and duration of finger strokes, iv) surface area covered by the testers' finger path trails, as well as iv) finger path correlation with the surface of the target shape. Results show that blind users are generally capable of accessing simple shapes and graphics presented on a vibrating touch-screen. However, results also underline various issues, ranging over: prolonged response time (e.g., blind users require 1 min and 22 s on average to recognize a basic shape), reduced touch-screen surface coverage, and low correlation between the surface of the target shape and the tester's vibration trails. The latter issues need to be further investigated to produce optimal recipes for using touch-screen technology to support image accessibility for blind users.